ADMINISTRASI PUBLIK DALAM PERSPEKTIF EKOLOGI - Engkus, Engkus (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2017)
The factors of ecology are still problem in public administration implementation, at the least, there are 5 (five) ecological factors: economic,social structure, communication net work,pattern of  ideololgy/symbol, and political system.It’s thought to have been caused by fifth factors  not done optimally yet. The aim of the research for understanding that ecologically,the fifth factors influence in public administration.At the least, understanding that public administration is not only one stand, but influenced by ecological factors where public administration in a place, and also in local autonomy implementation policy, regency/municipality, ecologically to explore resources, either human resources or nature resources relate with administrative ecolology. The methodology use are qualitative, the first to library study, and study of factual comparative complately, with central issue in the beaucracy, especially in Indonesia. The study of ecological administrationhas been done along ago, and the top at 1960 decade with established Comparative Administration Group (CAG) by Fred Riggs as a leader. The conclusion of  the writer that study of administrative ecology have been relevantly until now and important to reasearch  continously.